LncRNA PRKCQ‐AS1 regulates paclitaxel resistance in triple‐negative breast cancer cells through miR‐361‐5p/PIK3C3 mediated autophagy. (14th March 2023) - Zheng, Shurong; Fu, Weida; Huang, Qidi; Zhou, Jieyu; Lu, Kangkang; Gu, Junwei; Ma, Ruimin; Guo, Guilong
Abstract: Paclitaxel (PTX) resistance is a key cause of chemotherapy failure in patients with triple negative breast cancer (TNBC). The aim of this study is to investigate the effect and mechanism of long non‐coding RNA (lncRNA) on the PTX resistance of TNBC cells through autophagy. MDA‐MB‐231 cells are used to induce the PTX‐resistant TNBC cell line MDA‐MB‐231.PR (MDR) by increasing dose intermittently. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to validate the mRNA levels of phosphoinositide‐3‐kinase class 3 (PIK3C3), miR‐361‐5p and lncRNA PRKCQ‐AS1 in the cells, and Western blot analysis was used to detect the protein expressions of PIK3C3, autophagy‐related, drug‐resistant and apoptosis‐related genes. MDC staining detected the formation of autophagic vacuoles. The interactions between miR‐361‐5p and PIK3C3 and between lncRNA PRKCQ‐AS1 and miR‐361‐5p were verified by dual‐luciferase assay. Cell viability, apoptosis, migration and invasion were assessed by performing MTT, flow cytometry assay, and transwell assay. The mRNA level of miR‐361‐5p and the autophagy and drug resistance levels of TNBC PTX‐resistant cells were significantly up‐regulated. miR‐361‐5p could target autophagy‐related gene PIK3C3, and overexpression of miR‐361‐5p could down‐regulate PIK3C3 protein expression and autophagy level and PTX resistance of MDR cells. LncRNA PRKCQ‐AS1 was selected through bioanalysis, and miR‐361‐5p could target lncRNA PRKCQ‐AS1. In addition, lncRNA PRKCQ‐AS1 level was up‐regulated in TNBC PTX‐resistant cells, and knockdown of lncRNA PRKCQ‐AS1 could weaken autophagy and drug resistance level and could promote cell apoptosis. Overexpression of lncRNA PRKCQ‐AS1 reversed the pro‐apoptotic effect and down‐regulation of autophagy and resistance levels was induced by miR‐361‐5p. In vivo experiments were performed to verify the role of lncRNA PRKCQ‐AS1. We demonstrate that down‐regulation of lncRNA PRKCQ‐AS1 weakened PTX resistance and promoted cell apoptosis by miR‐361‐5p/PIK3C3 mediated autophagy.